ANALISIS PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN KEPUASAN KERJA TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL INTERVENING (Studi pada Perawat RSUP Dr.Kariadi, Semarang) - Prabowo, Adhityo; Djastuti, Indi (Faculty of Economics and Business Diponegoro University, 2014)
In the service industry, employee who performs direct contact with consumers is representatives of the organization and representatives ofÂ organization service quality itself. Hospital as one of organization which prioritize the quality of service, are required to be able to provide the best services for the patients satisfaction. nurse is one of the hospital elements who contributed in the quality of service, hence nurseâ€™s behavior plays an important role in the service of a hospital. The purpose of this study is to analyze the influence of transformational leadership and work satisfaction to organizational citizenship behavior with the organizational commitment as intervening variable.This research used primary data which obtained from the distribution ofÂ questionnaires through proportional random sampling technique to 92 nurses of RSUP Dr.kariadi, Semarang. Analysis of data in this research used multiple linear regression and sobel test for mediation effect testing.The result showed that transformational leadership and work satisfaction have positive and significant effect to organizational commitment. transformational leadership, work satisfaction and organizational commitment have positive and significant effect to organizational citizenship behavior. The result of this research also showed that organizational commitment is a strong antecedent to organizational citizenship behavior and a good mediation variable in mediating the influence of transformational leadership and work satisfaction to organizational citizenship behavior